Inventarisation and Study of Sere kedele Quality in Local Market in Gianyar Regency - Widyantari, Made Dwi; Suparthana, I Putu; Permana, I D. G. Mayun (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2018)
The aims of this research was to determine and inventory diversity of sere kedele production process traditionally in Gianyar Regency and to know the different of nutritional aspect on sere kedele produced. This research was conducted in 2 stages. The first stage is a survey to obtain information on materials and production equipment and sere kedele processing. The data obtained are tabulated and presented descriptively. The second stage is the analysis of nutritional components of sere kedele that includes water content, ash content, protein content, fat content and carbohydrate content. The results of the research in the first stage shows that in Gianyar Regency there are 3 subdistricts that produce sere kedele Sukawati, Gianyar and Blahbatuh, there are variations in the processing method used include boiling duration, fermentation length, spice addition technique before and after fermentation and fermentation container used closed and somewhat open. The results of the second stage of research showed that the nutritional components of   sere kedele includes water content ranges from 56.89% to 64.65%, ash content ranges from 1.56% to 2.42%, protein content ranges from 14.90% to 20.93%, fat content ranges between 5.34% to 9.50% and carbohydrate content ranges from 10.81.% to 12.97%.